2022
DOI: 10.1371/journal.pbio.3001682
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and epigenetic dysfunctions underlie the arrest of in vitro fertilized human embryos in a senescent-like state

Abstract: Around 60% of in vitro fertilized (IVF) human embryos irreversibly arrest before compaction between the 3- to 8-cell stage, posing a significant clinical problem. The mechanisms behind this arrest are unclear. Here, we show that the arrested embryos enter a senescent-like state, marked by cell cycle arrest, the down-regulation of ribosomes and histones and down-regulation of MYC and p53 activity. The arrested embryos can be divided into 3 types. Type I embryos fail to complete the maternal-zygotic transition, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 98 publications
0
10
0
Order By: Relevance
“…Aneuploidy is a common feature of cancer, although the role of aneuploidy in transformation remains unclear (Chunduri & Storchova, 2019). A normal karyotype is required for post-implantation embryonic development (Shahbazi et al , 2020), but may not be incompatible with pluripotency (Gaztelumendi & Nogues, 2014; Taapken et al , 2011; Yang et al , 2022). To rule out the impact of karyotype abnormalities on reprogramming capability we confirmed a normal karyotype for four of the lines that the subsequent study will mainly focus on ( Figure S2j ).…”
Section: Resultsmentioning
confidence: 99%
“…Aneuploidy is a common feature of cancer, although the role of aneuploidy in transformation remains unclear (Chunduri & Storchova, 2019). A normal karyotype is required for post-implantation embryonic development (Shahbazi et al , 2020), but may not be incompatible with pluripotency (Gaztelumendi & Nogues, 2014; Taapken et al , 2011; Yang et al , 2022). To rule out the impact of karyotype abnormalities on reprogramming capability we confirmed a normal karyotype for four of the lines that the subsequent study will mainly focus on ( Figure S2j ).…”
Section: Resultsmentioning
confidence: 99%
“…There is evidence that the longer the in vitro cultures last (i.e., blastocyst transfer in comparison to the cleavage stage), the more epigenetic changes occur [ 65 , 66 ]. We know that only a percentage of fertilized oocytes arrive at the blastocyst stage in vitro and recent observations suggest that metabolic and epigenetic dysfunctions underlie the arrest of human ART embryos before their compaction [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chromosomal abnormalities inherited from gametes or that occur during preimplantation development are major causes of implantation failure, miscarriage, and other abnormalities [62, 63]. Previous studies have suggested that aneuploidies contribute to embryonic arrest, and the levels of aneuploidy can be greater than 70% in human embryos [17]. In this study, we observed that blastomeres from arrested eight-cell embryos were more prone to CNVs than blastomeres from blastocyst-developed eight-cell embryos, which indicates that aneuploidies are likely associated with developmental delay of preimplantation embryos in cattle.…”
Section: Discussionmentioning
confidence: 99%
“…Developmental block of embryos produced in vitro remains the major concern in assisted reproductive technologies used in domestic animals [14]. Cattle are one of the most economically valuable livestock species, but the in vitro rate of blastocyst formation of bovine embryos is inefficient at only 20-40% [15][16][17][18]. Therefore, improvement to the blastocystformation rate of bovine embryos produced in vitro is the principal and urgent goal for efficient in vitro embryo production.…”
Section: Introductionmentioning
confidence: 99%